Association study of polymorphisms in the ABO gene and their gene‐gene interactions with ischemic stroke in Chinese population. Issue 4 (6th October 2017) - Li, Hao; Cai, Yong; Xu, An‐Ding
Abstract : Aims: To investigate the impact of 4 single nucleotide polymorphisms (SNPs) within ABO gene and their gene‐gene interactions on ischemic stroke (IS) susceptibility in Chinese Han population. Methods: A total of 1993 participants (1375 males, 618 females) were selected, including 991 IS patients and 1002 normal controls. The SNPstats (http://bioinfo.iconcologia.net/SNPstats ) was used for Hardy‐Weinberg equilibrium (HWE) test. Generalized multifactor dimensionality reduction (GMDR) was used to screen the best interaction combination among 4 SNPs within ABO gene. Logistic regression was performed to calculate the ORs (95%CI) for interaction between SNPs. Results: Both rs579459 and rs505922 within ABO gene were associated with IS risk in additive and dominant models. IS risks were higher in those with minor alleles of rs579459 and rs505922 than those with wild‐type homozygotes, OR (95%CI) were 1.62 (1.19‐2.10) and 1.69 (1.23‐2.18), respectively. We did not find any relation of rs651007 and rs529565 with IS risk in both additive and dominant models. GMDR model indicated a significant two‐locus model ( P  =   .0010) involving rs505922 and rs579459, indicating a potential interaction between rs505922 and rs579459, the cross‐validation consistency of the two‐locus models was 9/10, and the testing accuracy was 60.72%. We also found that participants with rs505922‐ TC/CC and rs579459‐ TC/CC genotype have the highest IS risk, compared to participants with rs505922‐ TT and rs579459‐ TT genotype, OR (95%CI) was 2.94 (1.28‐4.66). Conclusions: We found that rs579459 and rs505922 within ABO gene and their interaction were both associated with increased IS risk in Chinese population.